1987
DOI: 10.1159/000153741
|View full text |Cite
|
Sign up to set email alerts
|

AcP and EsD Polymorphisms in Central Sardinia

Abstract: A sample of the population from Central Sardinia was studied with respect to acid phosphatase (AcP) and esterase D (EsD) enzymes. The gene frequencies were: AcPA = 0.322, AcPB = 0.617, AcPC = 0.061 and EsD1 = 0.892. The results were compared with those of other Italian populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
1

Year Published

1988
1988
1992
1992

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
1
2
1
Order By: Relevance
“…They also were in equilibrium. The ACPI gene frequen cies found in the present survey are differ ent from those reported by Floris-Masala et al [1986] for Southern Sardinia (ACPI *A = 0.326 ±0.014, ACPI*B = 0.607 ±0.014 and ACPI*C = 0.067 ± 0.007) and from those by Lunesu et al [1987] for Central Sardinia (0.322 ± 0.018, 0.617 ±0.019 and 0.061 ± 0.009), but in agreement with those quoted by Piazza et al [1985] for four Central-Eastern Sardi nia villages (0.241 ±0.016. 0.646±0.0I8 and 0.113 ±0.012) and those by Modiano et al [1986] for total Sardinia (0.247 ± 0.009.…”
Section: Resultscontrasting
confidence: 94%
See 1 more Smart Citation
“…They also were in equilibrium. The ACPI gene frequen cies found in the present survey are differ ent from those reported by Floris-Masala et al [1986] for Southern Sardinia (ACPI *A = 0.326 ±0.014, ACPI*B = 0.607 ±0.014 and ACPI*C = 0.067 ± 0.007) and from those by Lunesu et al [1987] for Central Sardinia (0.322 ± 0.018, 0.617 ±0.019 and 0.061 ± 0.009), but in agreement with those quoted by Piazza et al [1985] for four Central-Eastern Sardi nia villages (0.241 ±0.016. 0.646±0.0I8 and 0.113 ±0.012) and those by Modiano et al [1986] for total Sardinia (0.247 ± 0.009.…”
Section: Resultscontrasting
confidence: 94%
“…A similar situation is found with re spect to other European populations in [Mourant et al, 1976;Tills et al, 1983]. Regarding to both ESI) and PGM I, the X2 analysis for the heterogeneity within Sardinia did not show any significant dif ferences between our sample and those re ported by Floris et al [1984], Floris-Masala et al [1986], Modiano et al [1986] and Lunesu et al [1987], However a statisti cally significant difference ( p < 0.001) was found for PGM I between this study and the data reported by Floris-Masala et al [Piazza et al, 1982;Rickards et al, 1984]. However, these two genetic markers do not allow a discrimination of Sardinians from other European popula tions [Papiha andNahar.…”
Section: Resultssupporting
confidence: 90%
“…In this note we report the distribution of three enzyme polymorphisms, adeny late kinase (AK), phosphoglucomutase (PGMi) and 6-phosphogluconate dehy drogenase (6PGD), in the Central Sardi nian population previously studied by us with respect to other polymorphisms [1]. Earlier we have examined the AK, PGM and 6PGD polymorphisms in the South ern Sardinian population [2,3].…”
mentioning
confidence: 97%
“…The aim of this paper is to report the distribution of Gc and C3 polymorphisms in a sample of the Central Sardinian popu lation previously studied by us with re spect to other polymorphisms [1,2].…”
mentioning
confidence: 99%